A Facile Synthesis of N-Boc-azocan-5-one - Morales-Chamorro, Maricela; Vázquez, Alfredo (Synthesis, 2019)
The azacycloalkane 1-azocan-5-one is embedded in the structure of several products of natural origin displaying a variety of bioactivities. Two convenient and straightforward routes were developed to synthesize N-Boc-azocan-5-one from readily available raw materials featuring a ring-closing metathesis (RCM) reaction as the key step.
Keywords: azocanone; nitrogen heterocycles; ring-closing metathesis; synthesis